The Role Of Brand Image As A Mediator Variable Of The Influence Of Brand Ambassador Marc Klok On Purchase Intention Of Mills Products In The Bandung City Area - Yoga Mubaraq; Triaji Prio Pratomo (Universitas Telkom, 2025)
Purchase intention emanates from consumers' inclination to acquire a product, influenced by processes of observation and education. Within the sports apparel sector, the implementation of robust marketing strategies is pivotal for sustaining and augmenting consumer purchase intention. Mills, a purveyor of sports attire, utilizes the strategy of engaging brand ambassadors to enhance its brand image and bolster purchase intention. Bandung, as the city contributing the most athletes to Indonesia across various sports, serves as the focus of this research. The objective of this research is to examine the mediating function of brand image in moderating the impact exerted by the brand ambassador, Marc Klok, on the intention to purchase Mills products within Bandung. A descriptive quantitative approach was employed, with analyses performed through the application of SmartPLS 3.2.9 for model evaluation. It has been revealed that the brand ambassador's direct influence on purchase intention is not substantial; however, a notable impact on brand image is observed. In turn, brand image markedly affects purchase intention and serves as a crucial mediator linking the brand ambassador to purchase intention.